2020
DOI: 10.3390/antibiotics9040164
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Colistin Resistance Links Cell Membrane Thickness Alteration with a Point Mutation in the lpxD Gene in Acinetobacter baumannii

Abstract: Acinetobacter baumannii is one of the most common causes of nosocomial infections in intensive care units. Its ability to acquire diverse mechanisms of resistance limits the therapeutic choices for its treatment. This especially concerns colistin, which has been reused recently as a last-resort drug against A. baumannii. Here, we explored the impact of gaining colistin resistance on the susceptibility of A. baumannii to other antibiotics and linked colistin resistance acquisition to a gene mutation in A. bauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Whole-genome sequencing analysis of the Col-R A. baumannii strains revealed that, the main causes of the resistance to colistin were mutations in the pmrA-pmrB genes, including pmrAP102 → R, pmrBP233 → S, pmrBT235 → N, and the novel alleles pmrAI13 → M and pmrBQ270 → P (Sun et al, 2020). Similar to our work, Saleh et al (2020) reported that two amino acid substitutions (A95 → T and P157 → R) in the transmembrane domains of PmrB cause low-level resistance to colistin.…”
Section: Discussionsupporting
confidence: 86%
“…Whole-genome sequencing analysis of the Col-R A. baumannii strains revealed that, the main causes of the resistance to colistin were mutations in the pmrA-pmrB genes, including pmrAP102 → R, pmrBP233 → S, pmrBT235 → N, and the novel alleles pmrAI13 → M and pmrBQ270 → P (Sun et al, 2020). Similar to our work, Saleh et al (2020) reported that two amino acid substitutions (A95 → T and P157 → R) in the transmembrane domains of PmrB cause low-level resistance to colistin.…”
Section: Discussionsupporting
confidence: 86%
“…Although colistin sulfate is the last resort for the treatment of A. baumannii infections, colistin resistance has been reported in 60% of strains in our study, and this higher rate is recently documented previously [ 37 , 40 , 41 ]. Correspondingly, some studies revealed that colistin retains its effectiveness against A. baumannii in Egypt (4.5%, and 7.4%) by El-Masry and Masry and Elsherbeny et al, respectively [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 69%
“…The mutations in lipid A biosynthesis genes, lpxA, lpxC , and lpxD , cause total loss of LPS production halting colistin binding to membrane and hence colistin resistance. There are mutations in the first three genes of the LPS production and therefore complete loss of the LPS layer ( 19 , 192 ).…”
Section: Resistance Mechanisms In Enterobacteriaceaementioning
confidence: 99%